Clinical results of short external rotators preserving posterolateral approach for hemiarthroplasty after femoral neck fractures in elderly patients. Issue 3 (March 2022) - Yoo, Je-Hyun; Kwak, Daekyung; Lee, Yongmin; Ma, Xiao; Yoon, Joonhyeok; Hwang, Jihyo
Highlights: The dislocation rate of hemiarthroplasty is still not lower than total hip arthroplasty. Short external rotators preserving shows significant decrease of postoperative reduction. This study shows 0.3%. SER preserving technique can be encouraging technique in hemiarthroplasty in the elderly. Abstract: Introduction: Even though the dislocation rate is lower in the hemiarthroplasty (HA) than total hip arthroplasty, it has still developed as one of serious complications in elderly patients. We have used short external rotators (SER) preserving posterolateral approach to reduce dislocation after hip arthroplasty, especially in elderly patients. The present study was conducted to introduce SER preserving posterolateral approach and report the dislocation rate after HA via this approach in elderly patients with femoral neck fractures. Methods: Between January 2015 and July 2019, 307 consecutive elderly patients aged over 70 years who underwent cementless bipolar HA for femoral neck fractures and were followed up for at least one year, were enrolled in this study. All surgeries were performed using the SER preserving posterolateral approach. The demographic and perioperative data were examined and the complications including dislocation were investigated. Results: Mean operation time was 54.3 min, and mean estimated blood loss was 252.4 cc. The mean follow-up time was 22.1 months, HHS was 67.5 points at the final examination Dislocation following HA developed in only one patient (0.3%) with dementia during hospital stay, which was reduced closely with no subsequent recurrence. Periprosthetic femoral fracture occurred in two patients, which was treated with internal fixation in one patient and with stem revision in the other patient. There was no surgical site infection or periprosthetic infection as complications. Conclusion: The SER preserving technique in posterolateral approach effectively can be effective for reducing the dislocation after HA in elderly patients with femoral neck fracture. It can be encouraged in posterolateral approach for HA, especially in elderly patients under the risk of dislocation.